Kepemimpinan Perempuan dalam Perspektif Islam - Raihan Putry (Jurnal Mudarrisuna: Media Kajian Pendidikan Agama Islam, 2015)
Leadership is no longer based on talent, ancestry, experience and male gender alone, but more than that physical and mental readiness of men and women in a planned towards professionalism. All the program is done through planning, analysis and development systematically to raise stamina attributes. Leadership in accordance with the spirit of the Shari'ah.